Penguatan Manajemen Laboratorium dalam Menurunkan Morbiditas dan Mortalitas Hepatitis B - Aditea Etawati Putri; Yetti Hernaningsih; Puspa Wardhani; Diah Puspita Rini; Yulia Nadar Indrasari; Nanda Aulya Ramadhan (Faletehan Health Journal, 2025)
Hepatitis B virus (HBV) infection is one of the threats in the medical world and requires guaranteed and valid laboratory analysis procedures, one of which is through the quality control (QC) mechanism. As part of laboratory management, QC has an impact on the validity of laboratory analysis results, especially related to HBV infection. The purpose of this study was to determine the level of knowledge of medical analysts before and after laboratory management training. The research method used comparative paired test analysis to obtain the significance and binary logistic regression to determine the most influential questions on the test. The results showed a significant increase in medical analyst knowledge after being given laboratory management material. Supported by a p value = 1.000 from the Hosmer and Lemeshow test and an overall prediction of 95.5% (positive: 92.0% and negative 97.6%), this training was very good in terms of goodness-of-fit and accurate. Material related to immunochromatography (ICT) method is an influential factor based on the analysis of test results. Medical analyst training, especially related to laboratory management in the context of HBV management, has a significant impact and can be continued and developed.